Honey application as a halal replacement material for fillet fish product in transportation - Muhammad Athoillah Sholahuddin (Journal of Halal Product and Research)
Fish is a food that is consumed by many people because fish contain high nutrition. Fillet products are diversification of fishery products that are quite popular with the community. That is because fillet products are easy to consume and have good nutritional content. However, fish fillet products are easily degraded during transportation. So that triggers traders to use hazardous materials in the form of formalin to increase the shelf life of fillet products. The shelf life of fish fillet products needs to be improved in order to obtain good quality and not be easily damaged by storing fillets at low temperatures and the addition of active ingredients in the form of honey. Honey also has antimicrobial properties so that it can be used as a food preservative. Honey can inhibit the growth of bacteria that cause decay. The purpose of this study was to determine the effect of adding honey with different concentrations on the shelf life of white pomfret (Pampus argenteus) fillets at cold temperatures. This research was experimental by making honey solutions with different concentrations (0%: 10%; 11%). This research uses a completely randomized design (CRD). The shelf life test is done by calculating the value of TPC, Protein, pH, Tvbn, and organoleptic. TPC, Protein, pH, TVBN, and organoleptic test results showed that the addition of honey with different concentrations had a significant effect on the shelf life of white pomfret fish fillets. The best concentration of adding honey is at a concentration of 5%. While the shelf life that can be accepted by consumers can reach 6 days shelf life. The results showed that honey can be used as an alternative preservative in fish fillet meat that functions as an antimicrobial and fat oxidation prevention.